Factor invariance of deviant conduct measures: A transcultural study with Portuguese, Argentinian and Brazilian teenagers (Research, Society and Development, 2021)
The deviant conducts practiced by teenagers are seen as behaviors that go against social norms and order, even though they are configured as a very harsh reality in several countries, both from specialists’ research and according to statistics. The present paper aims at assessing the empiric validity of the factor structure of the Scale of Anti-Social and Criminal Conduct (SCS) in different countries. It is an assessment measure of the deviant conducts that has been frequently used with different samples and which can be seen as conducts that interfere in people’s rights and duties and threaten their social and individual welfare. The study encompassed 411 teenagers, that is, 137 in each country, with ages ranging from 13 to 18 (M = 15.71; DP = 1,65; Mo = 15). The results show that the SCS factor structure was consistent. They also confirmed the bi-factor organization of such measure seen in Brazilian studies. Moreover, their factor invariance stands out in samples from the countries researched, which assesses CFI in the samples. This position shows that SCS presents high quality, and it also means that such phenomenon is very close to respondents in different social and political contexts concerning its construct. Thus, it can be stated that SCS is reliable and safe when there is the intention to assess deviant conducts in teenagers.